VALUE RELEVANCE OF ACCOUNTING INFORMATION AND MANAGERIAL ABILITY ( Manufacturer Companies at Indonesia Stock Exchange ) - HAZM, AFWIAN ASHFI (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objectives of this study to test theoretically the value relevance of accounting information and the value relevance of managerial ability. The value relevance of accounting information involve the value relevance of earning per share and the value relevance of book value equity. In addition, the purpose of this study also examines how managerial ability to measuring the relationship between accounting information and stock prices in manufacturing companies  listed  on  the  Indonesia  Stock  Exchange  (BEI)  in  2014-2016.  This  study  uses purposive sampling method in determining the number of samples used, and obtained 67 companies used as samples. This study uses secondary data sources. In this study the managerial skills  are  measured  using  Data  Envelopment  Analysis,  Data  is  analyzed  using  moderate regression analysis. The results showed that managerial ability have value relevance to measure firm value, through value of Earning Per Share and Book Value Equity. Keywords: value relevance,  earning per share,  book value equity, managerial  ability, Data Envelopment Analysis (DEA).